Rapid detection of type II diabetes mellitus in Saudi patients via simultaneous screening of multiple SNPs - Jumana Al-Aama (Biotechnology & Biotechnological Equipment, 2019)
A large-scale DNA-based assay, namely SNaPshot, was developed and validated for the determination of allelic polymorphisms of genes associated with type II diabetes (T2D) mellitus disease in Saudi patients. The new approach is alternative to phenotyping and physiological diagnosis. The assay includes single nucleotide polymorphisms (SNPs) of seven most common genes namely, GNB-3, GCK, SLC30A, KNJ11, TCF7L2, CDKN2A/B and HNF4A. The study proved that the new genotyping assay is rapid, easy to perform and robust for screening of high risk T2D family members. The new assay can be applied in genetic testing as an important tool for identifying significant genetic factors that help in predicting diabetes at early stages of life to avoid subsequent complications. This assay can also be used to evaluate the gene risk variants in populations of other geographic origins.